Simulation of pavement deformations for different approach SLABS concept constructed on Batu Pahat Soft Clay (BPSC) - Mohd Daud, Mohd Nazrin (2007)
Depression or bump that occurs between end of bridge approach slab and road pavement interface always arises a great concern among motorists. The occurrence of the bump that motorist feel as they leaves or approaches the bridge is caused by the differential settlement problem. This problem becomes more apparent particularly over soft soil condition such in Batu Pahat district. Currently, there is no guideline and specification provided by the Public Work Department in designing a proper bridge approach model, which has exceptional transition toward road pavement. The current conventional model used in many projects was reported to be less effective since the problem is still noticeable and it requires regular maintenance work when the problem reappears recurrently. Practically, it is clear that the problem is still unresolved and this is due to the complexity of the design problem itselfthat merge the structural and geotechnical perspectives in design. The studies on simulation modelling for approach slab and road pavement design also have been rare. It is essential since such design analysis, which is based on numerical analysis, could have advantages in providing preliminary expected outcomes for the modelling purpose. In conjunction to this matter, the modelling of several approach slab and road pavement concepts have been successfully conducted to verify the result expectancies using this approach in order to provide better understanding on the recurrent problem. Keywords: bump, bridge approach slab, differential settlement, soft soil, simulation modelling